HEPATIC INVOLVEMENT IN PARACOCCIDIOIDOMYCOSIS - Barbosa, William; Andrade, Ana Lúcia S. S. (Revista de Patologia Tropical / Journal of Tropical Pathology, 2007)
Paracoccidioidomycosis involves the liver and/or the bile ducts in a considerablenumber of patients with the acute disseminated form of the disease in the lymphaticabdominal type. It may produce fatty degenerative changes in the hepatic parenchyma,acute hepatitis, chronic granulomatous hepatitis, moderate portal fibrosis andoccasionally marked necrosis. These changes are accompanied by jaundice. Frequentlyobstrutive extrahepatic jaundice dominates the clinicai manifestations.